THE ROLE OF THE HALAL INDUSTRY IN IMPROVING THE ECONOMY AND ALLEVIATING POVERTY POST-COVID-19 PANDEMIC IN INDONESIA - Samsul Arifai (International Journal Mathla’ul Anwar of Halal Issues, 2023)
As the world's largest Muslim-populated country, Indonesia has the potential in developing the halal industry as one of the pillars of improving the economy and reducing poverty, which is still relatively high in Indonesia. This study aims to examine the role of the halal industry in improving the economy and reducing poverty in Indonesia, as well as efforts to optimize the role of the halal industry. The method used in this study is qualitative descriptive, which is conducted by reviewing relevant literature sources related to the topic. Data used in this study were obtained from various sources such as scientific journals, books, and reports from government agencies and international organizations related to the halal industry and poverty in Indonesia. The results show that the halal industry has a significant role in improving the economy, such as contributing to GDP, export growth, investment growth, and increasing employment opportunities. Efforts to increase the role of the halal industry in poverty reduction include integrated halal standards and certification, increasing public knowledge and awareness of halal products, developing export markets for halal products, improving halal product quality, strengthening halal certification institutions, encouraging collaboration between the halal industry and the government, and developing a holistic halal industry ecosystem.